A Detailed Profile of Union - Non-Union Wage Inequality in Canada: 1997-2004 - Easton, Mark David (University of Waterloo, 2006)
This thesis is focused on examining the extent of union-nonunion wage inequality in Canada from 1997 to 2004, using data from the Canada Labour Force Survey collected by Statistics Canada. The research is either directly or indirectly guided by two main measures of union-nonunion wage inequality. The first measure is the wage differential , which examines the difference between the union and nonunion wage after controlling for other relevant factors in a regression model; and the second measure is an account of wage dispersion or wage spread, which effectively explains how internally equitable the union-nonunion wage distribution is in relation to the average wage, after controlling for other relevant factors in a regression model. Each chapter tackles a different hypothesis or subject relating to Canadian union-nonunion wage inequality as investigated from the Canada Labour Force Survey Dataset, and is guided by an effort to explore issues or patterns not previously addressed in the extant literature. The initial analyses found that the union-nonunion wage differential across Canada was normally eleven to sixteen percent from 1997 to 2004. The research also examined three advanced topics in Canadian union-nonunion wage inequality. Analyses of the industry, occupational, and demographic trends in Canada over the past eight years showed that there is some evidence to suggest that demographic changes in union density does affect union-nonunion wage inequality, but this relationship is not conclusive. This research also addressed the unusual finding of higher hourly wages among parttime females. This difference was not present after conducting a more rigorous regression analysis within both sectors. However, it was found that the marginal male wage premium could largely be explained by the combined effects of establishment size among males in the union sector, as well as educational attainment among males in the union sector. Further investigation of some unexpected interaction effects of union status and establishment size and union status and job tenure in relation to the wage, revealed that these combined effects still generated comparative over the nonunion group, but only up to a certain level of tenure or establishment size. Finally, an analysis of whether union density has mattered at all in Canada for promoting higher wages, reveals that the general effects of union density on the wage are relevant only within a certain wage range and within certain industries.
Keywords: Social sciences